IMPACT OF INFLATION ON MAIN FOOD COMMODITIES PRICES IN CENTRAL JAVA (2019-2021) - Aulia, Aisyah (Transpublika Publisher, 2022)
Food commodities play an important role as a source in meeting the needs of people's lives. Price changes are common in food commodities and a contributor to inflation. This analysis aims to determine the effect of food commodity prices on inflation with a case study of commodity prices of rice, cooking oil, and sugar in Central Java. This type of research is a quantitative research. The data used in this study is secondary data obtained from BPS (Central Statistics Agency) of Central Java Province and PHPI from 2019 to 2021. The data used is monthly data which consists of 4 components of research data. The analytical method used is ECM (Error Correction Model). Processing data using Eviews 10 software by going through several processes or stages in the analysis that includes the ECM test so that the effect is in the short and long term. The results of this study indicate that the results of the ECM (VAR) test have not had a significant effect on the prices of the 3 food commodities.